Influence of Perceived Quality and Brand Image towards Purchase Decision of Indomilk UHT Milk in Pedurungan - Salma - Aqila; Noor - Suroija; Jati - Nugroho (Admisi dan Bisnis, 2023)
This study aims to determine the influence of Perceived Quality and Brand Image towards Purchase Decision of Indomilk UHT Milk in Pedurungan Semarang. The samples used were 100 respondents, the primary data collection method used interview and questionnaire. The sampling technique used a Non Probability Sampling technique with Accidental Sampling. The data analysis tools were using validity and reliability tests. The analysis technique used multiple linear regression. The results obtained from this study were the influence of perceived quality towards purchase decision partially hasn’t a significant influence and the influence of brand image towards purchase decision has a significant influence. Simultaneously perceived quality and brand image have an influence towards purchase decision. Based on the linearity test results on classical assumption test, it showed that the relationship between perceived quality towards purchase decision have a non-linear relationship between each variables and brand image towards purchase decision have a linear relationship between each variables. The results of the coefficient determination ( between perceived quality and brand image contributes jointly towards purchase decision by 40,2%, while the remaining 59,8% is determined by another variables which not examined in this study.